TERMINOLOGY MANAGEMENT IN THE TRANSLATION OF OIL AND GAS INDUSTRY DOCUMENTS - Nurmamatova Oysulton Erkinovna; Mirzayeva Gulasal (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION   Terminology Management in the Translation of Oil and Gas Industry Documents This article examines the significance of terminology management in the translation of oil and gas industry documents. The oil and gas sector relies heavily on specialized terminology, technical standards, and industry-specific concepts that require accurate and consistent translation. The study investigates the challenges faced by translators when dealing with technical terms, abbreviations, and multilingual documentation. It also  analyzes  modern  terminology  management  tools,  translation  memories,  and terminology  databases  that  contribute  to  translation  quality  and  efficiency.  The research  employs  qualitative  analysis  of  technical  documents  and  professional translation practices within the energy sector. The findings demonstrate that effective terminology  management  enhances  translation  accuracy,  reduces  ambiguity,  and facilitates international communication among stakeholders in the oil and gas industry.